THE ROLE OF DESTINATION IMAGE IN MEDIATING THE INFLUENCE OF HALAL LIFESTYLE AND SOCIAL MEDIA ON MUSLIM TOURISTS' DECISIONS TO VISIT BALI ISLAND - Yuliana Kumala Purnama Rade; Rahmat Ingkadijaya; Husen Hutagalung (Adisam Publisher, 2026)
This study aims to analyze the influence of halal lifestyle and social media on Muslim tourists' decision to visit Bali, with destination image as a mediating variable. This is a quantitative study using statistical analysis with sampling techniques, resulting in 132 respondents as the research sample. The research method used is quantitative with a Structural Equation Modeling (SEM-PLS) approach. The study found that: 1. Halal lifestyle has a positive and significant effect on Muslim tourists' decision to visit Bali. 2. Halal lifestyle has a positive and significant effect on the image of Bali as a destination. 3. Social media has the strongest and most significant effect on the decision to visit. 4. Social media has a positive and significant effect on destination image. 5. Destination image has a positive and significant effect on visit decisions. 6. Destination image mediates the effect of halal lifestyle on visit decisions. 7. Destination image mediates the effect of social media on visit decisions.